Penerapan Model Pembelajaran Project Based Learning Pada Kompetensi Menjahit Kemeja Keterampilan Tata Busana Siswa Kelas XI MAN 2 MadiunThis study aimed to analyze the implementation of the Project Based Learning (PjBL) model and to determine students’ le - Laila Nur Rohmah; Imami Arum Tri Rahayu (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aimed to analyze the implementation of the Project Based Learning (PjBL) model and to determine students’ learning outcomes in the competency of shirt sewing among eleventh-grade students at MAN 2 Madiun. The study was based on the need for a learning model that encourages active student participation while developing practical skills required in vocational education. This research employed a quantitative approach using a pre-experimental one-shot case study design. The sample consisted of 15 students selected through a total sampling technique, in which all members of the population were included as research participants. Data were collected through classroom observations to examine teacher and student activities during the learning process, as well as through product assessments of the men’s shirts produced by the students. The data were then analyzed using descriptive quantitative methods by calculating the mean score for each assessment indicator. The findings revealed that the implementation of the PjBL model was categorized as excellent. This was indicated by the average teacher activity score of 3.58 and the average student activity score of 3.71. Furthermore, the students’ learning outcomes achieved an average score of 3.96, equivalent to 79.2. All students met the predetermined mastery criterion, resulting in a 100% mastery rate. These findings indicate that the implementation of Project Based Learning effectively promotes active student engagement in the learning process and contributes positively to improving learning outcomes in the competency of shirt sewing.